Existence of Hilfer Fractional Evolution Inclusions with Almost Sectorial Operators - Mian Zhou; Yong Zhou (Mathematics)
In this paper, we mainly focus on the the existence of Hilfer fractional evolution inclusions with almost sectorial operators. For two cases in which the almost sector operators are compact and noncompact, we obtain existence criteria for mild solutions, which extend and improve some related results in the literature.